2021
DOI: 10.1155/2021/2695793
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Assessment of Antimicrobial Susceptibility of Periodontopathic Bacteria in Peruvian Patients with Periodontitis: A Pilot Study

Abstract: Background. Severe periodontal disease is highly prevalent worldwide, affecting 20% of the population between the ages of 35 and 44 years. The etiological epidemiology in Peru is scarce, even though some studies describe a prevalence of 48.5% of periodontal disease in the general population. Periodontitis is one of the most prevalent oral diseases associated with site-specific changes in the oral microbiota and it has been associated with a socioeconomic state. This study aimed to determine the etiology and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Fifteen studies ( Gamboa et al, 2013 , 2014 ; Ehrmann et al, 2014 ; Xie et al, 2014 ; Collins et al, 2016 ; Bhardwaj et al, 2017 ; De-la-Torre et al, 2017 ; Arredondo et al, 2019 , 2020 ; Bhat et al, 2019 ; Mínguez et al, 2019 ; Almeida et al, 2020 ; Ardila and Bedoya-Garcia, 2020 ; Irshad et al, 2020 ; Aguilar-Luis et al, 2021 ) were conducted in a University/Dentistry College. Three studies were conducted in a public dental clinic ( Binta and Patel, 2016 ; Akrivopoulou et al, 2017 ; Ansiliero et al, 2021 ), and other three studies were conducted in private clinics ( Rams et al, 2011 , 2014b , 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifteen studies ( Gamboa et al, 2013 , 2014 ; Ehrmann et al, 2014 ; Xie et al, 2014 ; Collins et al, 2016 ; Bhardwaj et al, 2017 ; De-la-Torre et al, 2017 ; Arredondo et al, 2019 , 2020 ; Bhat et al, 2019 ; Mínguez et al, 2019 ; Almeida et al, 2020 ; Ardila and Bedoya-Garcia, 2020 ; Irshad et al, 2020 ; Aguilar-Luis et al, 2021 ) were conducted in a University/Dentistry College. Three studies were conducted in a public dental clinic ( Binta and Patel, 2016 ; Akrivopoulou et al, 2017 ; Ansiliero et al, 2021 ), and other three studies were conducted in private clinics ( Rams et al, 2011 , 2014b , 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies reported chronic periodontal infection ( Gamboa et al, 2014 ; Bhardwaj et al, 2017 ; De-la-Torre et al, 2017 ), two studies reported a diagnosis of aggressive infection ( Akrivopoulou et al, 2017 ), six studies reported a diagnosis of severe/moderate infections ( Rams et al, 2011 , 2014a , 2014b , 2020 ; Binta and Patel, 2016 ; Bhat et al, 2019 ), two studies reported more than one type of infection ( Collins et al, 2016 ; Arredondo et al, 2020 ), and 11 studies did not report the diagnosis of periodontal infection ( Gamboa et al, 2013 ; Ehrmann et al, 2014 ; Xie et al, 2014 ; Dhotre et al, 2015 ; Arredondo et al, 2019 ; Mínguez et al, 2019 ; Uribe-Garcia et al, 2019 ; Almeida et al, 2020 ; Irshad et al, 2020 ; Aguilar-Luis et al, 2021 ; Ansiliero et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%